Validation of extended theory of reasoned action to predict mobile phone money usage - Otieno, Odoyo Collins; Liyala, Samuel; Odongo, Benson Charles; Abeka, Silvance O.; Ogara, Solomon O. (Horizon Research, 2018)
Theory of Reasoned Action (TRA), postulated by social psychologist, has been established to be relevant in guiding Information Systems studies. The theory resulted from attitude research using the Expectancy Value Models. Therefore, TRA can be more effective if extended with additional determinants/constructs of systems use. The purpose of this study was to validate the additional constructs expected to strengthen TRA. Both qualitative and quantitative research methods were used in compilation of this paper. Additional determinants have therefore been validated using correlation and are illustrated in this article to demonstrate their effects on technology use in an Information Systems discourse. To achieve this, the authors used the findings from a study that was conducted in setting that presented rural urban characteristics, varied social economic characteristic as well as the varied age sets. The paper puts clearly the possibility of applying the theory of reasoned action in an information systems discourse, with additional constructs, giving birth to the Extended Theory of Reasoned Action.
DOI: 10.13189/wjcat.2018.060101
Keywords: Information Systems; Theory of reasoned action; TRA; Extended theory of reasoned action